2019
DOI: 10.3390/su11205762
|View full text |Cite
|
Sign up to set email alerts
|

Doing Good Better: Impure Altruism in Green Apparel Advertising

Abstract: In this study, we identify impure altruism as a duality of altruistic and egoistic warmth. We examine how these feelings motivate consumers to buy green apparel in response to advertisements. We test the effectiveness of the message orientation and its interactivity with a beneficiary and propose modeling impure altruism as the reason why consumers purchase green apparel. The study uses a quasi-experiment to estimate a comparison effect among advertising stimuli. We conduct an online survey among US consumers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
(129 reference statements)
1
33
0
1
Order By: Relevance
“…Part of our respondents may have endorsed pure egoistic values, which are expected to negatively relate to pro-environmental consumption patterns. Another part of our respondents may have felt self-conscious and proud of being associated with a green imago [30]. However, another part may have associated green products with health benefits, and their egoistic value orientations may have been positively associated with their sustainable consumption pattern.…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 97%
See 3 more Smart Citations
“…Part of our respondents may have endorsed pure egoistic values, which are expected to negatively relate to pro-environmental consumption patterns. Another part of our respondents may have felt self-conscious and proud of being associated with a green imago [30]. However, another part may have associated green products with health benefits, and their egoistic value orientations may have been positively associated with their sustainable consumption pattern.…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 97%
“…With respect to Hypothesis 1a-c, we found that the expected negative relationship between egoistic value orientations and green consumer patterns was not confirmed by our data. This finding may be the consequence of the fact that egoism encompasses feelings of pride and self-respect, which are derived from self-interest [30]. Previous research has found that self-conscious and egoistic feelings are positively related to prosocial behaviours because acting pro-socially makes egoistic individuals feel proud of themselves [61].…”
Section: Discussion and Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seriousness of environmental problems may not reach a sufficiently malignant level to activate self-interest. Song and Kim [ 98 ] also proposed that the public may have dual motives of benefitting others and themselves when they have an awareness of the harmful environmental consequences, then feel egoistic and altruistic concerns jointly, correspondingly. In our research, people in Taiwan have a strong perception that air pollution is the most serious of all environmental problems, with negative consequences for their own and others’ health and safety.…”
Section: Discussionmentioning
confidence: 99%